Pengaruh E-Service Quallity, E-Trust, dan E-Satisfaction terhadap E-Loyality Pelanggan Shopee (Studi Kasus Mahasiswa Universitas Islam Malang Angkatan 2019) - Aqilla Tasya Ramadhani; Muhammad Agus Salim; Ita Athia (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the factors that influence e-loyalty. These factors are e-service quality, e-trust and e-satisfaction. This study examines consumer loyalty to shopee customers. The purpose of this study is to determine the effect of e-service quality, e-trust and e-satisfaction on e-loyalty of shopee customers. Data were analyzed using quantitative methods by distributing questionnaires. The sample in this study were 90 respondents and data processing using SPSS. The analytical tools used in this research are validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis test, and adjusted R square test. This research has fulfilled the validity test and reliability test. The results of testing the first hypothesis (H1) are accepted that e-service quality, e-trust and e-satisfaction have a significant positive effect on e-loyalty with a significance level of 0.000. The second hypothesis (H2) is accepted which shows that there is a significant positive effect between e-service quality on e-loyalty with a significance level of 0.025. The third hypothesis (H3) is accepted which shows that there is a significant positive effect between e-trust on e-loyalty with a significance level of 0.031. The fourth hypothesis (H4) is accepted which shows that there is a significant positive effect of e-satisfaction on e-loyalty with a significance level of 0.000.The results of this study conclude that the variables that influence e-service quality, e-trust and e-satisfaction have a simultaneous and partial effect on e-loyalty of shopee customers. Keywords: e-service quality, e-trust, and e-satisfaction, e-loyalty.